Murray’s system of needs and the Big Five Personality Traits: Using Exploratory Structural Equation Modeling to evaluate their relationship - Anunciação, Luis (2025)
Personality tests are used regularly as a requirement within many sectors in Brazil, including education, human resources, and transportation. The Personality Factor Inventory, based on Murray’s system of needs theory, is one of the widely used tools within Brazil. Despite its importance, its results are only partially related to the Big Five theory, which is the predominant framework for understanding personality. This theoretical divergence poses practical challenges for professionals who rely on or are required to work within the Big Five model. Harmonizing these two theories could enhance their practical utility. In this study, we evaluate the possibility of fitting Murray’s personality theory within the Big Five framework using Exploratory Structural Equation Modeling and invariance tests (i.e., gender) using data from 272 845 participants in Brazil (56.2% men, M age 21.74 ± 15.24) who completed the Personality Factor Inventory. We also cross-validated the results with random samples. The results demonstrated an adequate fit, consistent reliability, and scalar/strong invariance. The percentage of Murray’s theory factor into the Big Five solution led us to conclude that Murray’s system of needs could fit into a five-factor solution reflecting the Big Five personality traits. The paper discusses the implications of these findings for future research and practice.